2018 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--31110
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the EWB Design Summit on the Professional Social Responsibility Attitudes of Participants

Abstract: in Melbourne. He has worked in 10 countries on 5 continents, and as a consultant and facilitator with UNESCO, Australian Volunteers International, Engineers without Borders, Scope Global, World Vision, and the Victorian Curriculum and Assessment Authority. He also has a regular radio segment as "Dr Scott", answering listeners' questions about science. Dr. Nick John Brown, Engineers Without Borders AustraliaNick Brown leads the research interests and activities of Engineers Without Borders Australia. Nick is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…As shown by Jessup, Sumner, and Barker (2005), Coyle, Jamieson, and Oaks (2006), and Selingo (2006), service-learning is popular with women. Daniel and Brown (2018) showed that a long-running service-learning program run by EWB (Australia) has non-quota enforced percentage of approximately 45% women out of more than 1000 students. Interestingly, Bauer et al (2007) shows a greater awareness to community service from female students compared with male students.…”
Section: Experiential Learning and Service-learningmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown by Jessup, Sumner, and Barker (2005), Coyle, Jamieson, and Oaks (2006), and Selingo (2006), service-learning is popular with women. Daniel and Brown (2018) showed that a long-running service-learning program run by EWB (Australia) has non-quota enforced percentage of approximately 45% women out of more than 1000 students. Interestingly, Bauer et al (2007) shows a greater awareness to community service from female students compared with male students.…”
Section: Experiential Learning and Service-learningmentioning
confidence: 99%
“…Service-learning may therefore help attract and retain female engineering students at universities, it may improve the educational experience of those female students, and society may gain more benefit from female students undertaking service-learning programs compared with male students. Beyond gender diversity, Desmond, Stahl, and Graham (2011), show a link between service-learning and diversity education in a broader context.…”
Section: Experiential Learning and Service-learningmentioning
confidence: 99%